Synthesis and adsorption application of amine shield-introduced-released porous chitosan hydrogel beads for removal of acid orange 7 from aqueous solutions. Issue 77 (22nd August 2015) - Li, Tingting; Liu, Yunguo; Wang, Shufan; Zeng, Guangming; Zheng, Bohong; Wang, Hui; Zhang, Mingming; Guo, Fangying; Zeng, Xiaoxia
<x xml:space="preserve">Abstract</x> An effective and low-cost adsorbent named amine shield-introduced-released porous chitosan hydrogel beads (APCB) was synthesized and used for the removal of acid orange 7 from aqueous solutions.